2019
DOI: 10.1177/1934578x19896684
|View full text |Cite
|
Sign up to set email alerts
|

Betulin Protects HT-22 Hippocampal Cells against ER Stress through Induction of Heme Oxygenase-1 and Inhibition of ROS Production

Abstract: A key pathologic event in neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease, is endoplasmic reticulum (ER) stress-induced neuronal cell death. ER stress-induced generation of reactive oxygen species (ROS) has been implicated in neurological disease processes. Betulin is one of the major triterpenoids found in Betula platyphylla that possesses several biological properties, including cytoprotective and antioxidative effects. Therefore, we investigated whether betulin could prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…One of our previous studies has reported the anti-inflammatory potential of A. subulatum (Drishya et al, 2021). Results of the present study showed acid (Kilic & Yesiloglu, 2013;Pragasam et al, 2013), syringic acid (Li et al, 2018), ferulic acid (Mahmoud et al, 2020), gallic acid (Badhani et al, 2015;Kroes et al, 1992), catechin (Fan et al, 2017), naringenin (Chung et al, 2019;Rashmi et al, 2018), rutin (Selloum et al, 2003;Yang et al, 2008), costunolide (Eliza et al, 2010;Nan et al, 2020), betulin (Lee et al, 2019), villosin (Li et al, 2016), n-hexadecanoic acid (Aparna et al, 2012), and so forth are some of the bioactive phytoconstituents in MEAS, which were reported to exhibit antioxidant/ anti-inflammatory potential. Hence, it can be concluded that the presence of these bioactive phytoconstituents confers A. subulatum the protective effect against MTX toxicities, suggesting the possibility of a combined therapeutic approach with MEAS so as to subside severe toxicities of MTX therapy.…”
Section: Ta B L E 4 Effect Of Meas On Serum Hepatotoxicity Markers Fo...supporting
confidence: 56%
See 1 more Smart Citation
“…One of our previous studies has reported the anti-inflammatory potential of A. subulatum (Drishya et al, 2021). Results of the present study showed acid (Kilic & Yesiloglu, 2013;Pragasam et al, 2013), syringic acid (Li et al, 2018), ferulic acid (Mahmoud et al, 2020), gallic acid (Badhani et al, 2015;Kroes et al, 1992), catechin (Fan et al, 2017), naringenin (Chung et al, 2019;Rashmi et al, 2018), rutin (Selloum et al, 2003;Yang et al, 2008), costunolide (Eliza et al, 2010;Nan et al, 2020), betulin (Lee et al, 2019), villosin (Li et al, 2016), n-hexadecanoic acid (Aparna et al, 2012), and so forth are some of the bioactive phytoconstituents in MEAS, which were reported to exhibit antioxidant/ anti-inflammatory potential. Hence, it can be concluded that the presence of these bioactive phytoconstituents confers A. subulatum the protective effect against MTX toxicities, suggesting the possibility of a combined therapeutic approach with MEAS so as to subside severe toxicities of MTX therapy.…”
Section: Ta B L E 4 Effect Of Meas On Serum Hepatotoxicity Markers Fo...supporting
confidence: 56%
“…Mitigating effect of MEAS against MTX‐induced toxicities is attributed to the antioxidant and anti‐inflammatory properties exhibited by bioactive phytoconstituents in MEAS. Vanillic acid (Calixto‐Campos et al., 2015; Kumar et al., 2011), p‐coumaric acid (Kilic & Yesiloglu, 2013; Pragasam et al., 2013), syringic acid (Li et al., 2018), ferulic acid (Mahmoud et al., 2020), gallic acid (Badhani et al., 2015; Kroes et al., 1992), catechin (Fan et al., 2017), naringenin (Chung et al., 2019; Rashmi et al., 2018), rutin (Selloum et al., 2003; Yang et al., 2008), costunolide (Eliza et al, 2010; Nan et al., 2020), betulin (Lee et al, 2019), villosin (Li et al., 2016), n‐hexadecanoic acid (Aparna et al., 2012), and so forth are some of the bioactive phytoconstituents in MEAS, which were reported to exhibit antioxidant/anti‐inflammatory potential. Hence, it can be concluded that the presence of these bioactive phytoconstituents confers A .…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Glutamate is a toxicant that induces oxidative stress in HT22 cells causing severe damage and neuroexcitotoxicity [ 17 ]. HT22 cells were exposed to glutamate (4 mM) in the presence of isolated compounds at the concentration ranging from 0.1 to 10 μM for 24 h ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lee and co-workers revealed that betulin could protect Hom cells cultured in a medium. A betulin extract with a concentration of 15.625 µg/mL could protect T-22 hippocampal cell viability against reactive oxygen species-stressed cytotoxicity [32]. As a result of the zebrafish experiments, it was concluded that betulin extract has negative cytotoxicity and shows potential for use in food and pharmaceutical applications.…”
Section: Hacat Cell Viability Of the Betulin Extractmentioning
confidence: 97%
“…This can probably be attributed to the unfavorable effect of impurity compounds in the extract. Hofmann et al reported that each antioxidant activity assay is specific to certain types of antioxidants, and none of the assays evaluate the overall antioxidant capacity of a plant extract [32]. Therefore, combined multi-assay methods for antioxidant activity evaluation may be propitious to pursuing complex antioxidant properties in betulin extracts.…”
Section: In Vitro Antioxidant Activities Of the Betulin Extractmentioning
confidence: 99%